All of this is true a novel - Penaflor, Lygia Day (Harper Teen, an imprint of HarperCollinsPublishers, 2018)
When Long Island teens Miri, Soleil, Penny, and Jonah befriend a bestselling YA novelist, they find their deepest, darkest secrets in the pages of her next novel, with devastating consequences. Told from different perspectives as interviews, journal entries, and book excerpts.